Psychological Capital Mediation on the Relationship between Auditor Experience and Acceptance of Under-Reporting Time: An Indonesian Study - Faiz Zamzami; Syaiful Ali; Dina Natasari (Universitas Muhammadiyah Malang, 2021)
This study aimed to examine the auditor's psychological capital and psychological capital mediation experience on the relationship between the auditor's experience and the acceptance of under-reporting time. To maintain the quality of audit report results, efforts are needed to prevent dysfunctional behavior from auditors. It is also necessary to determine the factors that trigger dysfunctional behavior, especially under-reporting time. This study uses online surveys with respondents from government auditors who work at the Supreme Audit Agency, spread across regional offices throughout Indonesia. Sixty-nine respondents participate in this study. The results showed a relationship between auditors’ experience, psychological capital, and under-reporting time acceptance. This study proves that experience influences psychological capital and psychological capital mediates the relationship between experience and acceptance of under-reporting time. The result contributes to the literature's psychological capital. This study is the first to introduce the relationship between psychological capital, auditor experience, and under-reporting time acceptance.